Statistics for economics, accounting and business studies - Barrow, Michael (FT Prentice Hall, 2006)
This is a core text for introductory courses in statistics at undergraduate and MBA level. The book will be particularly suitable for economics and accounting students and will also appeal to business studies students. The fourth edition of Statistics for Economics, Accounting and Business Studies presents an exceptionally clear and concise introduction to a range of statistical concepts and techniques. Using actual data to illustrate the text, this student-friendly book shows how real-life problems can be solved using statistical techniques and explains why particular techniques are used. Throughout the text key issues are highlighted and many common statistical traps and mistakes are revealed and explained. Aimed at students of economics and the closely related disciplines of accountancy and business, this user-friendly text requires no prior knowledge of the subject and provides students with numerous real-life examples, problems and applications.